The Impact of FDI on Innovation and Networking Activity in Central and Eastern Europe - A Patent Analysis - Mirja Meyborg (European Regional Science Association (ERSA), 2010)
Introduction After the impact of four decades of socialism, Central and Eastern Europe (CEE) were only endowed with backward technology. To achieve sustainable economic growth rates, it was necessary to foster technology transfer and modernisation (see Solow, 1956, Romer, 1990). In this sense, CEE governments advanced the view that foreign direct investment (FDI) could play a significant role in supporting these 'latecomers' to establish a domestic technology and knowledge base (see Bailey et al.,1999). Hence, the question arises, whether FDI fosters innovation and networking activities in CEE, and in how far a domestic technology and knowledge base could be build up. Methodology Patent statistics are a crucial tool for economic and innovation research. They measure the successful output of R&D efforts (see Carpenter and Narin, 1983, Griliches, 1984, and Schmoch et al., 1988). In this paper, patent data are used, in order to measure innovation activities. As innovation-indicator, patents refer to technological innovations, mirroring a part of the existing knowledge stock of a sector, region, or economy (see Frietsch, 2007). Besides, by means of patent data, inventor networks are filtered. Breschi and Lissoni (2003) already remarked that networks that include members from more than one company spread knowledge freely among these companies. Last, an FDI analysis is made for CEE, in order to determine, if FDI plays a significant role for innovation and networking activities. The FDI analysis is broken-down to NUTS3-level where possible. Empirics This analysis consists of the examination, if FDI affects innovation and networking activities in CEE, i.e. if those regions that received most FDI are also front-runners in patent filing and possess a high connectivity within the European innovation networks. Thereby, the Social Network Analysis (SNA) shed light on the importance of each country in the inventor network. Simultaneously, other variables are considered in order to estimate whether they play a significant role in this regard, or, if a high grade of regional FDI concentration brings about growth within other variables, such as share of skilled labour force, share of subsidies within the tertiary sector, and persons employed in research institutes and universities.
Keywords: 330; Innovation Activity; Foreign Direct Investment; Central and Eastern Europe; Patent Analysis; Social Network Analysis